Salvinorin A: A hallucinogenic terpene present in Salvia divinorum Epling & Játiva (2017)
Theme and scope: The objective of this review is to present the chemical studies that have been carried out on Salvia divinorum E&J in recent years. Characteristics: Since the 1990s, the distribution and use of Salvia divinorum E&J has increased for “recreational purposes” due to its hallucinogenic effects and easy access. Its effects on the body have been linked to other substances such as: delta-9-THC in marijuana, DMT, LSD , MDMA, PCP and ketamine. Findings: Chemical research carried out in other countries on Salvia divinorum E&J focuses on the extraction, determination, quantification, analysis and biosynthesis of Salvinorin A, a chemical compound that is attributed to the bioactivity of the plant. This compound is considered as one of the most potent hallucinogens of natural origin, in addition to being chemically and structurally unique, since it was the first known diterpene with psychoactive activity. Conclusions : In the last years, the chemical research into Salvia divinorum E&J have focused, on several matrices such as leaves, blood, urine and water, using gas chromatography and liquid chromatography, in order to determine Salvinorin A and other metabolites present in the plant. In one piece of research, it was demonstrated by NMR and HR-ESI-MS that the biosynthesis of Salvinorin A is given by the mevalonic acid metabolic pathway and the methylerythritol phosphate pathway, which correspond to the metabolic pathways for terpene biosynthesis.